Partial discharge detection for breakdown identification / Mohd Elmy Shapie - Shapie, Mohd Elmy (2011)
This thesis presents partial discharge detection for breakdown identification of a distribution cable. Partial Discharge is one of the main causes of underground cable failure in operation. Therefore it is the responsibility to the power utility such as Tenaga Nasional Berhad (TNB) to ensure the continuous and optimum electricity delivery to the consumers. The presence of partial discharge in an underground cable need to be detected before it can cause breakdown to the cable insulation. Therefore it is suggested that the jointing quality need to be improved to prevent insulation failure on the jointing of cross-linked polyethylene (XLPE) cable and the aging cable above 20 years which needs to be replaced by paper insulated lead cable (PILC).